2002
DOI: 10.1109/78.995062
|View full text |Cite
|
Sign up to set email alerts
|

Optimal designs for space-time linear precoders and decoders

Abstract: In this paper, we introduce a new paradigm for the design of transmitter space-time coding that we refer to as linear precoding. It leads to simple closed-form solutions for transmission over frequency-selective multiple-input multiple-output (MIMO) channels, which are scalable with respect to the number of antennas, size of the coding block, and transmit average/peak power. The scheme operates as a block transmission system in which vectors of symbols are encoded and modulated through a linear mapping operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
508
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(515 citation statements)
references
References 27 publications
5
508
0
2
Order By: Relevance
“…The average transmit power E s for diagonal precoders is choosen large enough such that the power is always allocated on both virtual subchannels. It is observed that the N-d min solution is better than WaterFiling [1], max-λ min [3] and MMSE [6] precoders in terms of d min .…”
Section: B For Qpsk Modulationmentioning
confidence: 91%
See 2 more Smart Citations
“…The average transmit power E s for diagonal precoders is choosen large enough such that the power is always allocated on both virtual subchannels. It is observed that the N-d min solution is better than WaterFiling [1], max-λ min [3] and MMSE [6] precoders in terms of d min .…”
Section: B For Qpsk Modulationmentioning
confidence: 91%
“…They are designed to optimize various criteria such as maximizing the minimum singular value [3], maximizing the post-processing SNR [5], and minimizing the mean square error (MSE) [6]. These precoding matrices are all diagonal and lead to power allocation strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when channel state information (CSI) is available at the transmitter, linear precoding can be used to further improve system performance by tailoring the transmission to the instantaneous channel conditions [2]- [5] while retaining the benefits of alllinear processing. CSI at the transmitter is mandatory in the multiuser downlink, where a base station attempts to communicate simultaneously with multiple users.…”
Section: Iintroductionmentioning
confidence: 99%
“…To efficiently exploit the multi-antenna hardware, an important issue in MIMO system design is to optimize the source precoding matrix [1], [2]. A general framework of optimizing the source precoding matrix has been developed in [2] by using the majorization theory [3].…”
Section: Introductionmentioning
confidence: 99%